Working out Egypt : effendi masculinity and subject formation in colonial modernity, 1870-1940 - Jacob, Wilson Chacko, 1972- (e-Duke books scholarly collection., 2011)
Historical study that looks at the centrality of the masculine body--particularly in sports and physical culture--to notions of modernity in colonial Egypt.